2022
DOI: 10.1088/1361-6463/ac761a
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Hubbard U parameter to explore accurate electronic and optical behaviour of BiFeO3

Abstract: Based upon Hubbard U corrected density functional theory (DFT), electronic and optical responses of multiferroic Bismuth ferrite (BiFeO3, BFO) have been critically explored. Treating BFO as a strongly correlated insulating system, a Hubbard U parameter is considered for accurate description of localized Fe-3d states. However, U parameter for Fe-3d state is not sufficient as 2p states of O atoms are greatly influenced by Fe-3d states. Similar U parameters for Fe-3d as well as O-2p states are considered. Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…All calculations were spin-polarized and a DFT-D3 dispersion correction scheme was used. 41 Based on Dudarev's implementation of the Hubbard model for a system of interacting electrons, 42 an effective on-site Coulomb interaction parameter (U eff ) of 4.0 and 4.3 eV was applied to Ti 43,44 and Fe, 45,46 respectively (except for the reaction energy barrier calculations, see below). The charge states on the oxide layers were assessed with a density-derived electrostatic and chemical method (DDEC6) as implemented in the chargemol program.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations were spin-polarized and a DFT-D3 dispersion correction scheme was used. 41 Based on Dudarev's implementation of the Hubbard model for a system of interacting electrons, 42 an effective on-site Coulomb interaction parameter (U eff ) of 4.0 and 4.3 eV was applied to Ti 43,44 and Fe, 45,46 respectively (except for the reaction energy barrier calculations, see below). The charge states on the oxide layers were assessed with a density-derived electrostatic and chemical method (DDEC6) as implemented in the chargemol program.…”
Section: Methodsmentioning
confidence: 99%
“…In systems with localized electrons, such as transition metal oxides and rare‐earth compounds, DFT often fails to capture the energy levels and electronic distribution correctly due to the presence of correlated electron interaction. To correctly explore the electronic structure, we introduced DFT + U to treat the strongly correlated d and f ‐states of Mo and rare‐earth ( RE = La, Ce, Pr, Nd, Sm) elements, respectively [25]. Furthermore, in the current study, total magnetic moments (μ tot ) were calculated, and the materials revealed ferromagnetic properties, except for CeMoN 3 , which exhibited an antiferromagnetic character.…”
Section: Introductionmentioning
confidence: 99%
“…In systems with localized electrons, such as transition metal oxides and rare-earth compounds, DFT often fails to capture the energy levels and electronic distribution correctly due to the presence of correlated electron interaction. To correctly explore the electronic structure, we introduced DFT + U to treat the strongly correlated d and f-states of Mo and rare-earth (RE = La, Ce, Pr, Nd, Sm) elements, respectively [25].…”
mentioning
confidence: 99%
“…2 because of the localized d electrons. This is a well-known issue in predicting the electronic structure of transition metals oxides[61][62][63][64][65]. Previously, for instance, Labat et al[66], Mattioli et al[62] and Di Valentin et al[67] have reported the band gaps of 2.08…”
mentioning
confidence: 98%